Durability and Strength Properties Self-Compacting Mortars with High-Calcium Fly Ash and Silica Fume - Benli, Ahmet; Karataş, Mehmet (My University, 2017)
This paper aims to investigate the strength properties and durability of self-compacting mortars (SCMs) produced from C class flyash (FA) and silica fume (SF) as mineral admixtures. SCMs were produced from the binary mixes of FA and SF by replacing Portlandcement with 10%, 20%, and 30% by weight of C class fly ash (FA) and 6%, 10%, 14% by weight of silica fume (SF). The water-tobinder(w/b) ratio ranges from 0.37 to 0.48. A sum of 7 different mixtures with 630 kg/m3 binder were prepared to observe SCMsbehavior in fresh and hardened conditions. Mini slump flow diameter, viscosity and mini V-funnel flow time tests were performed toassess the fresh properties of SCMs containing FA and SF. Specimens of 40x40x160 mm were produced and cured at the age of 7, 28and 180-day for compressive and tensile strength tests and 50 mm cube specimens were prepared and cured at 28 days for durabilitytests (porosity and density). The results indicated that the compressive strength of binary mixes of FA reduces as the content of FAincreases. Binary mix of SF10 reaches the highest tensile strength at the age of 180 days.
Keywords: İnşaat Mühendisliği; Malzeme Bilimleri; Özellik ve Test; Mühendislik; Kimya